Design and Build an Application for Psychology E-Counseling Services for Website-Based Students with the Prototype Method - Nabilla Nabilla; Arief Ichwani (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2022)
The role of the University as an institution of higher education and research, besides that the reason for the importance of psychological counseling services on campus aims to support students achieve academic success, psychological health, along with social and emotional well-being. Psychological counseling is important for students to understand their own behavior, emotions, and ideas. This is because students who have an interest in doing psychological counseling with counselors encounter problems in making appointments, which is that the counseling scheduling system is still done manually. Therefore, by implementing the Psychological E-Counseling system to support student activities or needs in making appointments on campus to make easier, more effective, faster, and facilitate psychological counseling services online and offline by utilizing the use of website applications. The final results obtained from this application research are using black box testing techniques to test the system built to run according to the design and as support the success of the application to make easier for Esa Unggul students who want psychological counseling, the Admin, and Counselors in serving counseling activities.Â